Quantitative Analysis of 137 MRI Images in Hydrocephalic Dogs - Hao Zhuang; Qiqing Yang; Lin Zhang; Xiaosong Xiang; Dandan Geng; Qiyun Xie; Changmin Hu (Veterinary Sciences)
With the increasing popularity of dogs as pets, cases of hydrocephalus have risen significantly. Due to the ongoing challenges in the diagnosis and treatment of hydrocephalus, advancements in magnetic resonance imaging (MRI) technology have greatly enhanced the diagnostic capabilities in small animal clinical practice. Assessing ventricular size is crucial for the clinical management of hydrocephalus and other neurological disorders. However, methods for quantifying ventricular size and evaluating the severity of hydrocephalus requires further optimization. This study involved 137 hydrocephalus and 17 normal dogs. In hydrocephalus cases, the maximum percentage of the ventricle height to brain height (H-max%) was correlated with the area (A-max%) and volume (V-max%). Equations were calculated based on these findings, showing that the percentage of height can effectively represent the percentage of area and volume, which can indicate the diagnosis and monitoring of hydrocephalus prognosis.